Os olhares das crianças sobre a cidade de Vitória/ES : a escola como um ponto de partida - Teixeira, Ana Moscon de Assis Pimentel (2012)
This study had the objective of investigating experiences with children from the neighborhood of São Benedito, which were related to their relationship with and in the social spaces in Vitoria, ES. The school was considered the starting point for the analysis of the conjuncture of the city. The methodology was qualitative and took the cartography as basis, which made possible to follow the processes of subjectivation and creation of sociability produced between and with the children. The theoretical references were authors who defend a conception of children seen as authors, historical and social subjects who belong to a geographic space, and who are able to appropriate and recreate culture. There is also a dialogue with authors that problematize the organization and the relations that are formed in the urban spaces of the contemporaneity. As a result, the study points to some analysis, highlighting that the city of Vitoria, in spite of its small geographic extension, shows great differentiation in use and appropriation by children from different social classes. Although the children from São Benedito have a broad view over Vitoria, the leisure sites are not very accessible to them. The school has an important role in their lives; however, the way it is organized imposes silence and denial of the children’s culture, which limits the possibilities for re-invention and participation. Thus, the children claim for spaces for meetings, discoveries, manifestation of freedom, and spaces that can promote other ways of sociability able to create bonds and opportunities for them to express their dreams and peculiarities, not only in the school, but also in their neighborhood and city. Thus, their desires and aspirations indicate the importance of potencializing a school and a city that have the condition to contribute so that the children can recognize themselves inside this historic, geographic, and social space in such way that they become capable of finding a place to belong and commit to the continuity of the world. Neighborhood, city, school and childhood, here is a structure that needs to be constructed inside the dynamics of the city, in order to give visibility to children and their cultures.